Purification and molecular properties of papaya pectinesterase - Fayyaz, A.; Asbi, B.A.; Ghazali, H.M.; Che Man, Y.B.; Jinap, S. (Elsevier, 1994)
Pectinesterase (EC 3.1.1.11) was extracted and purified from papaya (Carica papaya L. var. exotica). The procedure adopted for purification resulted in an approximate 250-fold purification (784 units/mg protein) with a 45% recovery of the pectinesterase activity. The enzyme was eluted in a single peak after CmdashSephadex and Sephadex G-100 chromatography. The purified enzyme had a uniform specific activity throughout the final chromatographic peak. The enzyme preparation was confirmed to be of homogeneous state by gel filtration and nondashdenaturing polyacrylamide gel electrophoresis and it has a molecular weight of approximately 32 000 Da.